1995
DOI: 10.1161/01.str.26.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Where and How Should Elderly Stroke Patients Be Treated?

Abstract: Well-organized management of elderly stroke patients was associated with a better outcome. It was also the more economical alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1
12

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(115 citation statements)
references
References 16 publications
3
99
1
12
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Meta-analysis of all available randomized controlled trials has shown that care of stroke patients in an SU reduces mortality, institutionalization, and dependency. 10,11 Why SU treatment works is still under discussion.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Meta-analysis of all available randomized controlled trials has shown that care of stroke patients in an SU reduces mortality, institutionalization, and dependency. 10,11 Why SU treatment works is still under discussion.…”
mentioning
confidence: 99%
“…They found that patients treated in the Neurology department were discharged earlier and had better functional outcomes after one year of follow-up. 11 As stated by Chadwick and Smith, seizures are also frequently misdiagnosed or over-treated prior to neurological evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that comprehensive coordinated care, as provided by the VA system, can improve functional outcomes and reduce the length of hospital or nursing home stays more than care in a traditional stroke unit [7][8][9][10][14][15][16][17][18][19]. The VA and the Department of Defense (DOD) recognized the need for care coordination for stroke patients in their publication of the Clinical Practice Guidelines for the Management of Stroke Rehabilitation 2003 (http://www.oqp.med.va.gov), as did the Commission on Accreditation of Rehabilitation Facilities, which introduced stroke specialty program standards for medical rehabilitation in 2005.…”
Section: Discussionmentioning
confidence: 99%